Masjid Sebagai Pusat Pengembangan Ilmu Keislaman Periode Klasik - Teguh Handoyo; Abdul Khobir (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The abstract is written in one paragraph with a single space (maximum 200 words), without any reference or formul This article discusses the growth and development of Islamic educational institutions from classical to modern times inseparable from the history of the mosque as an early institution in classical Islamic education. As the first institution built to educate the people after hijrah to Medina, the prophet made the mosque the main basis for the birth of civil civilization. The mosque not only functions as a place of worship but also serves social, cultural, political and security functions. It was in this mosque that religious education in its most basic form was given and developed into a center for the study of various Islamic sciences with teachers from the main companions with a halaqah teaching system that developed until now in modern Islamic boarding schools. The rapid development of the times resulted in the mosque transforming into a madrasa and resulted in the function of the mosque being reduced to a place of worship alone. Efforts to restore the function and role of the mosque as the center of civilization in modern times are again rife with the hope that a new civilization will emerge based on the mosque.